HUBUNGAN ANTARA SIKAP BELAJAR DENGAN HASIL BELAJAR MATA DIKLAT MENGGAMBAR DENGAN PERANGKAT LUNAK SISWA KELAS X KOMPETENSI KEAHLIAN TEKNIK GAMBAR BANGUNAN SMK NEGERI 2 SIJUNJUNG - 320-326 , Oon Zekri (CIVED, 2014)
ABSTRACT   This research aim to to express and know how big attitude relation learn to result learn eye of diklat draw with software of class student of X interest membership of Teknik Gambar Bangunan of SMKN 2 Sijunjung. This Research, background because still many student getting less gratifying value and getting value below Complete Criterion Minimize ( KKM).This Type Research have the character of descriptive by using method of korelasional. Sampel in this research is all class student of X Teknik Gambar Bangunan in SMK Negeri 2 Sijunjung that is 30 student people. Type and of sekunder which obtaining from result of student study at diklat draw with primary data and software which in obtaining to propagated kueisoner at class student of X Teknik Gambar Bangunan in SMKN 2 Sijunjung in period 2013 / 2014. Technique data collecting with scale of likert, technique analyse data of use descriptive analysis.Result of this research, is obtained degree of attainment of responder that is equal to 69,08 %, so also with result learn him also pertained is enough seen from mean mount attainment of result learn student equal to 73,17 %. There by can be expressed that there are relation between attitude learn with result learn student at eye of diklat draw with software of CAD, Interest Membership Of Teknik Bangunan Program Study Teknik Gambar Bangunan in SMK Negeri 2 Sijunjung.   Keyword : Relation, Attitude learn, Result learn.